Pelatihan Pembelajaran Inovatif Dan Kreatif Pada Guru Pondok Tahfidz Ahlul Jannah Desa Paddinging Kecamatan Sanrobone Kabupaten Takalar - Muh Azhar; Abdul Wahab; Abdul Qahar Zainal; Syamsul Bakhri (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Educator activities in Pondok Tahfidz Ahlul Jannah, Paddingging Village, Sanrobone District, Takalar Regency are currently mostly based on teaching and learning activities that are still carried out conventionally. Based on the results of the initial survey of the Proposal Team to Pondok Tahfidz Ahlul Jannah Paddinging Village, there are many teachers who need assistance and education related to creative and innovative learning systems so that the quality of human resources can be further improved, and students are less enthusiastic and less enthusiastic in following the formal learning process. Referring to the results of service, the various problems faced by Partners and their solutions are: 1. The learning system by teachers is still monotonous, teaching methods are still conventional which are like habits and habits applied by teachers, even though there are many strategies that can make students more creative and innovative in working such as making wall magazines, portfolio tasks, making handicrafts according to the cultural culture of the community. 2. Students are less enthusiastic about participating in learning, because the learning system still uses makeshift media, even though science and technology must move forward simultaneously, technological developments are very fast so teachers must master learning media as a companion in the learning process. Like the film surgery system, the presentation of material with power points that can make learning more interesting by displaying photos or videos related to the material delivered by the teacher. As well as many methods that can be applied to students to make creative and innovative such as discussions, expert teams, problem solving, film review, and action / role-playing. 3. The teaching method is only in the classroom, because according to this era, namely the 5.0 era, students are expected not only to understand theory but must understand practice and its use. Educators can use outdoor learning or field studies, so students can directly witness and Linking directly between theories obtained in books and in class. Be it social subjects, natural science subjects, religious sciences, science and technology and so on. The results of creative and innovative learning training are that teachers understand various multi-learning methods, teachers use media in delivering material such as power points and learning videos, students are directed to collaborate with their colleagues, understanding the film surgery system, where students are directed not just to watch but there are moral messages and wisdom that can be learned, and teachers understand outdoor learning or field observation.